Development of a family medicinal plant garden for Gunungmanik primary school students - Rinto Susilo; Aan Kunaedi; Didin Ahidin; Arsyad Bachtiar; Aris Slamet Widodo; Johan Johan; Muhamad Kusnendar; Suwarno Suwarno; M. Agung Miftahuddin; Gufron Amirullah; Ahmad Alfateh Rahanyamtel; Della Pariska; Hayatun Nega Amna; Hulman Taufik Azhar; Lala Komalasari; Muhammad Fikri Fanillah; Nanda Riandita Rizky Kinanti; Putri Dwi Jayanti; Rizky Fitra Ramadhan; Rizqah Sely Salsabil; Unggul Nirwikoro Prihadmoko (Universitas Muhammadiyah Magelang, 2023)
Gunungmanik Village is located in a highland area with significant potential in agriculture and plantations, as well as rich biodiversity. However, the potential of existing herbs has not been optimally developed. The aim of this community service is to empower the community and utilize natural resources through the cultivation of herbal plants. Activities include socialization, training, and mentoring for Gunungmanik primary school students. This program has successfully increased students' understanding of herbal plants and their maintenance techniques. Additionally, students have created a medicinal plant garden using plants from the surrounding environment in Gunungmanik Village. Consequently, this program offers educational benefits, especially for students, and promotes environmental conservation, particularly in relation to the herbal potential in Gunungmanik Village.